Striking Ethnic Disparities in Cardiometabolic Health in Albania: Divergent Burdens Across Minority Groups - Jonida Stefa; Brizida Refatllari; Gentiana Qirjako; Gabriele Kerr; Thomas Beaney; Ergys Ramosaçaj; Genc Burazeri (Journal of Racial and Ethnic Health Disparities, 2026)
Abstract Aim To assess disparities in chronic conditions among different ethnic minorities in Albania, controlling for demographic and behavioural factors. Methods The May Measurement Month campaign, a cross-sectional study recruiting adults through convenience sampling, was conducted in Albania in 2023 (MMM23). Three blood pressure measurements were recorded and a structured interviewer-administered questionnaire gathered information on participants’ demographics, behavioural factors, and preexisting conditions. Multivariable-adjusted binary logistic regression assessed the independent association of ethnicity with preexisting conditions. Results Overall, 14,869 individuals were recruited (aged 49 ± 15 years; 62% females; ethnicity: 93% Albanians, 5% Roma/Egyptian, and 2% other ethnic minorities). After adjustment for demographic and behavioural factors, relative to ethnic Albanians, Roma/Egyptian participants had significantly higher odds of hypertension (OR = 1.3, 95% CI = 1.1–1.6), diabetes (OR = 2.0, 95% CI = 1.6–2.4), previous myocardial infarction (OR = 2.7, 95% CI = 2.1–3.4), previous stroke (OR = 4.1, 95% CI = 3.2–5.3), heart failure (OR = 2.4, 95% CI = 1.9–3.1), and kidney failure (OR = 1.7, 95% CI = 1.3–2.2). Conversely, there was an inverse association between other ethnic minorities (mainly Greek) and hypertension (OR = 0.6, 95% CI = 0.4–0.7), diabetes (OR = 0.6, 95% CI = 0.4–0.9), previous myocardial infarction (OR = 0.4, 95% CI = 0.2–0.9), and kidney failure (OR = 0.3, 95% CI = 0.1–0.8) relative to ethnic Albanians. Conclusion Our findings reveal profound ethnic disparities in cardiometabolic health in Albania, with Roma/Egyptian minorities displaying elevated risks, suggesting embedded structural disadvantages. In contrast, other minorities showed inverse associations with several conditions, suggesting heterogeneity in risk profiles that merits further exploration. These disparities highlight the urgent need for equity-oriented health policies, culturally tailored prevention programs, and strengthened surveillance systems to ensure that marginalized populations in Albania are not left behind.